2020
DOI: 10.1039/c9nr10558a
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of coercivity of self-assembled stacking of ferrimagnetic and antiferromagnetic nanocubes

Abstract: The coercivity of magnetic nanoparticles is enhanced by the exchange coupling effect at the interface of ferrimagnetic and antiferromagnetic self-assembled monolayers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 51 publications
0
15
0
1
Order By: Relevance
“…The inherent particle-mediated nonclassical crystallization pathway of these processes has raised increasing scientific attention in more recent research [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. Consequently, researchers have discovered that the behavior of a controlled aggregation and self-assembly can further be utilized to create astounding new materials with exciting properties [ 6 , 15 , 16 , 17 , 18 , 19 ]. In particular, colloidal methods have been demonstrated to enable access to highly ordered structures with unique functionalities [ 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…The inherent particle-mediated nonclassical crystallization pathway of these processes has raised increasing scientific attention in more recent research [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. Consequently, researchers have discovered that the behavior of a controlled aggregation and self-assembly can further be utilized to create astounding new materials with exciting properties [ 6 , 15 , 16 , 17 , 18 , 19 ]. In particular, colloidal methods have been demonstrated to enable access to highly ordered structures with unique functionalities [ 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…47 Recently, it was shown that the coercivity of MNPs is enhanced by the exchange coupling at the interface of ferrimagnetic and antiferromagnetic selfassembled monolayers. 395 For this and similar systems, reectometry, GISANS, and XRMS can reveal the correlation between structural and magnetic ordering between the layers over a large size range with nanometer resolution. Micromagnetic simulations allow linking the microscopic structure to the corresponding macroscopic magnetic properties.…”
Section: Summary and Perspectivesmentioning
confidence: 93%
“…[36][37][38][39] Especially,a nisotropic nanoparticle assemblies have been of great interest due to their shape-dependent properties provided by an additional degree of freedom. [40][41][42][43] Research, however, has also laid out that the formation of BNSLs beyond layered membranes still remains am ajor issue until today.T othe best of our knowledge,nowork was reported on binary 3D mesocrystals despite their promising potential. Herein, we report the self-assembly of iron oxide (Fe 3 O 4 ) nanocubes (IONC) as well as platinum nanocubes (PtNC) into large mesocrystalline superstructures to demonstrate for the first time the formation of binary 3D mesocrystals containing both particle types.…”
Section: Introductionmentioning
confidence: 99%